12x-2(4x-9)=46

Simple and best practice solution for 12x-2(4x-9)=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-2(4x-9)=46 equation:


Simplifying
12x + -2(4x + -9) = 46

Reorder the terms:
12x + -2(-9 + 4x) = 46
12x + (-9 * -2 + 4x * -2) = 46
12x + (18 + -8x) = 46

Reorder the terms:
18 + 12x + -8x = 46

Combine like terms: 12x + -8x = 4x
18 + 4x = 46

Solving
18 + 4x = 46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 4x = 46 + -18

Combine like terms: 18 + -18 = 0
0 + 4x = 46 + -18
4x = 46 + -18

Combine like terms: 46 + -18 = 28
4x = 28

Divide each side by '4'.
x = 7

Simplifying
x = 7

See similar equations:

| x+5=-3x+10 | | 2x-11y=-3 | | 4y-2=-23-3y | | -2x+7=-4+12 | | =2a(4a^2-6a+8) | | 2x+9=51 | | -4j^7(-9j^6)= | | 3-2x=-4[4+5(2x-1)] | | 8t^2+6t-9=0 | | 3p+8=-16 | | 4t^2=-6t | | -8y+9=24 | | 5x=33x+9 | | 8t+17=2 | | 2a+6-a=10+a-4 | | 3=6b+21 | | 8(y-2)=-3(3) | | x-(33.125)=-5.27 | | =(3y^3+9y^2-11y+8)-(-4y^2+10y-6) | | x(33.125)=-5.27 | | 10x-2(4x-4)=24 | | 13-3h=-8+4h-7 | | 99=95-h | | 3x-8x+12=(3x-8x)+12 | | 99=94-h | | 75+5x=79+4x | | 3x+12-8x=3x-8x+12 | | 120=3x+15 | | 5y-6=y-6 | | 2y-6=-13-5y | | 3x+64=5x | | (5x+7)(4+6)= |

Equations solver categories